I.
First, plug in the number two in the place of x.
f(2) = 3(2) + 2.
Simplify
f(2) = 6+2
f(2) = 8
II.
First, we need to find the inverse function of x.
To do this, we begin by replacing f(x) with y, and switching the x and y values.
y= (2x-7)/3
x= (2y-7)/3
Then we solve for y.
3x = 2y-7
3x + 7 = 2y
(3x+7)/2 = y
Replace y with f^-1(x)
f^-1(x)= (3x+7)/2
Now that we have the inverse function, plug in 3 for x.
f^-1(x) = (3(3) + 7)/2
f^-1(x) = (9+7)/2
f^-1(x) = 16/2 = 8.
III. 2y+14 = 4y-2
Solve for y
14 = 2y - 2
16 = 2y
y = 8
So, since all of the statements have the result of 8, then all the statements have the same result.
Hope this helps!